2022
DOI: 10.3390/nu14030527
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Supplement of Probiotic Strains AP-32, bv-77, and CP-9 Increased Akkermansia mucinphila and Reduced Non-Esterified Fatty Acids and Energy Metabolism in HFD-Induced Obese Rats

Abstract: Obesity is referred to as a condition in which excess body fat has accumulated to an extent that it causes negative impacts on health. The formation of body fat is regulated by complicated networks in relation to energy metabolism, and gut microbiota have been regarded as a key player. Studies have shown that supplements of probiotics provide benefits to health, including an improvement in metabolic syndrome and the control of body weight. In the present study, three probiotic strains, AP-32, bv-77, and CP-9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Since energy metabolism is related to gluconeogenesis and the production of ketone bodies during starvation or diets with very low availability of digestible carbohydrates [ 223 ], more importance of analysing ketone bodies in the context of hypo- and more recently hyperglycaemic states in in vivo studies should be considered. Furthermore, the effect of probiotics on ketone body levels and energy metabolism reduction as well as their positive correlation, has been demonstrated in animal models [ 224 ].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Since energy metabolism is related to gluconeogenesis and the production of ketone bodies during starvation or diets with very low availability of digestible carbohydrates [ 223 ], more importance of analysing ketone bodies in the context of hypo- and more recently hyperglycaemic states in in vivo studies should be considered. Furthermore, the effect of probiotics on ketone body levels and energy metabolism reduction as well as their positive correlation, has been demonstrated in animal models [ 224 ].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…The tolerance of B. animalis CP‐9 to acid and bile salts was also demonstrated in this study. These properties of B. animalis CP‐9 increase the chance for the oral supplement of lyophilized powder to reach and colonize in the intestine, and the oral supplement of B. animalis CP‐9 was recently reported to modulate gut microbiota in high‐fat diet‐treated rats (Liao et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The multi-strain probiotic supplement used in this trial contained three species from two genera. The effects of mono- (AP-32, bv-77, or CP-9) and multi-strain (AP-32/bv-77/CP-9) probiotic supplementations have been previously investigated in obese rats ( 14 ). Consistent with the animal study, improved blood lipid profiles and gut microbiota modulation was observed in the subjects of this trial who received multi-strain probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a keen need to clarify specific probiotic strains or products that can provide positive effects on weight control in obese children. In our previous study, the weight-reducing effect of a multi-strain probiotic supplement was validated in high-fat diet (HFD)-induced obese rats ( 14 ). The multi-strain probiotic supplement contained three strains: L. rhamnosus bv-77, B. lactis CP-9, and L. salivarius AP-32.…”
Section: Introductionmentioning
confidence: 99%